Retrospective analysis of 471 surgically treated zygomaticomaxillary complex fractures. Issue 2 (February 2018) - Blumer, Michael; Kumalic, Sabina; Gander, Thomas; Lanzer, Martin; Rostetter, Claudio; Rücker, Martin; Lübbers, Heinz-Theo
Abstract: Purpose: Zygomaticomaxillary complex (ZMC) fractures are frequent in facial trauma; only fractures of the mandible are more common. Although the frequency of these fractures is geographically consistent, the aetiology differs widely among countries and even regions. Differences in socio-economic status and the ageing population seem to be two causes. This retrospective epidemiological study evaluates patients who were surgically treated for ZMC fractures at a Swiss university clinic. Materials and methods: This study included 471 patients who were surgically treated for ZMC fractures in an oral and maxillofacial surgery clinic at a Swiss university hospital between January 2004 and December 2012. Complicated fractures such as LeFort II/III and bilateral ZMC fractures were excluded. Data on gender, age, and type of trauma were recorded. Fractures were classified by aetiology: motorised road traffic (car or motorcycle), bicycle, interpersonal violence, sports, falls (both less than and greater than 3 m in height) and other causes. Results: A total of 350 patients were male (74%), and 121 were female (26%). The ZMC fractures were most likely to occur in the third decade (117 cases, 25%). A predominance of male patients was found in the young age groups, but an equal ratio was found in the elderly groups. Etiologically, falls of less than 3 m were the most common cause of ZMC fractures (125 cases, 27%). Interpersonal violence was second (88 patients, 19%); male patients dominated this group, which had a male-to-female ratio of 21:1. A predominance of male patients was found in every subdivision when analysing by aetiology and gender. The lowest proportion of males (57%) was found for falls of less than 3 m. Conclusion: In our study, interpersonal violence and falls outnumbered road traffic accidents among causes of maxillofacial fractures. This is probably a consequence of strict road and work laws. Additionally, the older and more active populations accounted for the highest proportion of falls, and young male patients were the predominant victims of ZMC fractures.